2020
DOI: 10.5812/semj.92018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacteria Contaminating Musca domestica (Diptera: Muscidae) Collected from Animal Husbandries

Abstract: Background: House flies (Musca domestica L.) may mechanically transmit many microorganisms to humans. Objectives: To identify bacteria contaminating Musca domestica (Diptera: Muscidae) collected from animal husbandries in province of Qom, Iran in the year of 2019. Methods: In the cross-sectional study, house flies were captured by plastic water bottle fly traps and insect nets from four districts of the Qom Province and were immediately transferred to the Department of Medical Entomology, School of Public Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…This agrees with Hussny et al [12] at Thi-Qar University, College of Science in Iraq Kababian et al [14], in Iran this study in Qom Province; Central Iran, Hemmatinezhad et al [17] in Iran and, all studies had a greater percentage of bacterial contamination in the digestive system than in the external surface. This shows that the inner surface may be most crucial for vectoring a wide range of ambient as well as harmful microorganisms.…”
Section: -Estimation Of Bacterial Content Of House Flies According To...supporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with Hussny et al [12] at Thi-Qar University, College of Science in Iraq Kababian et al [14], in Iran this study in Qom Province; Central Iran, Hemmatinezhad et al [17] in Iran and, all studies had a greater percentage of bacterial contamination in the digestive system than in the external surface. This shows that the inner surface may be most crucial for vectoring a wide range of ambient as well as harmful microorganisms.…”
Section: -Estimation Of Bacterial Content Of House Flies According To...supporting
confidence: 91%
“…Baker et al [13]In Iraq; at the University of Tikrit; the house flies are the source of the vector of contamination in bacterial infections; where the study showed the isolation of 9 types of bacteria which are harmful to people. Kababian et al [14], This research was conducted in Central Iran's Qom Province .Because the location and manner of collecting the flies, as well as the same health system and collection times, are all to blame for the results' convergence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be explained that the bacteria isolated from the two samples in the current research can be considered as food-borne pathogens in the different wards of the hospitals. Similarly, a previous study conducted by our team showed E. coli and P. aeruginosa were the most prevalent bacterial isolates detected in houseflies ( Musca domestica ) ( 41 ).…”
Section: Discussionsupporting
confidence: 68%
“…Musca autumnalis De Geer, 1776 may act as the source of trichostrongylate distribution. Muscina stabulans (Fallén, 1817) and Stomoxys calcitrans (Linnaeus, 1758) are known to be mechanical carriers of Ancylostoma caninum (Ercolani, 1859) larvae and Trichuris vulpis (Frölich, 1789) eggs respectively (Paliy et al, 2018;Kababian et al, 2020). The species diversity and the number of zoophilic flies vary depending on the type and age of potential hosts (vertebrates).…”
Section: Introductionmentioning
confidence: 99%